The effect of upstroke on monofin swimming speed in young athletes in underwater sports - Redi E. V.; Ivashko N. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to assess the impact of the upward movement on the swimming technique in a monolast and the rate of distance covered by athletes aged 12-13 who participate in underwater sports.